Mandate the president and the people - Kunhardt Productions; Annenberg Foundation Trust at Sunnylands ([Philadelphia, PA?] : Annenberg Foundation Trust at Sunnylands, 2006)
Examines the long and complex relationship between the presidency and public opinion. Scholars explore decisive moments in the history of the presidency from George Washington to FDR.
The founding Fathers through President Jackson -- President Lincoln and the Civil War -- President Franklin Roosevelt and the New Deal.
Narrated by Lesley Stahl.
DVD.
In English with subtitles in English and Spanish.
Keywords: Jackson, Andrew, -- 1767-1845.; Lincoln, Abraham, -- 1809-1865.; Roosevelt, Franklin D. -- 1882-1945.; Presidents -- United States -- History; Spanish language materials -- Video recordings; United States -- Politics and government; Video recordings for the hearing impaired